2015
DOI: 10.5152/eajm.2014.0016
|View full text |Cite
|
Sign up to set email alerts
|

Significant Association between Serum Levels of Von Willebrand Factor (vWF) Antigen with Stages of Cirrhosis

Abstract: Objective: Von Willebrand factor (vWF) is a mediator that increases endotoxemic medium like in cirrhosis. In this study we evaluated the association of serum VWF antigen (Ag) level with the stage of cirrhosis (according to Child-Pugh classification).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 17 publications
1
19
0
3
Order By: Relevance
“…Another possible mechanism of elevated VWF in cirrhosis is induction of synthesis of VWF in the liver with cirrhosis itself [13], or reduced liver-mediated clearance resulting from decreased expression or activity of ADAMTS13 (VWF-Ag cleaving protease) [14] which may further increase VWF-Ag levels in patients with cirrhosis with PHT. Yilmaz et al reported that plasma VWF-Ag level increase in cirrhotic patients and this is more pronounced with higher stages of cirrhosis according to Child-Pugh score [7]. Wu et al reported that the VWF is a noninvasive predictor of portal hypertension and OVs in patients with cirrhosis and increased levels of VWF in liver tissues may induce the elevated plasma VWF levels [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible mechanism of elevated VWF in cirrhosis is induction of synthesis of VWF in the liver with cirrhosis itself [13], or reduced liver-mediated clearance resulting from decreased expression or activity of ADAMTS13 (VWF-Ag cleaving protease) [14] which may further increase VWF-Ag levels in patients with cirrhosis with PHT. Yilmaz et al reported that plasma VWF-Ag level increase in cirrhotic patients and this is more pronounced with higher stages of cirrhosis according to Child-Pugh score [7]. Wu et al reported that the VWF is a noninvasive predictor of portal hypertension and OVs in patients with cirrhosis and increased levels of VWF in liver tissues may induce the elevated plasma VWF levels [15].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in patients with liver cirrhosis and portal hypertension reported that: plasma level of VWF-Ag is significantly higher with more progression and impairment of the condition and in patients with esophageal varices and in patients with clinically significant PHT (hepatic venous pressure gradient = HVPG ≥ 10 mmHg) [7] [8].…”
Section: Introductionmentioning
confidence: 98%
“…In hepatocytes, all proteins of the coagulative system are synthesized; these are procoagulants (with the exception of the Von Willebrand factor and blood clotting factor VIII), coagulation inhibitors (antithrombin III, proteins C, S, α2-macroglobulin, α-antitrypsin, etc. ), [7,8]. According to the literature, liver cirrhosis (LC) is characterized by a decrease in the number of such proteins in different proportions, which leads to an imbalance of procoagulants and anticoagulants.…”
mentioning
confidence: 99%
“…The work by Yilmaz et al [1] in The Eurasian Journal of Medicine provides clinical evidence for the correlation between increased levels of von Willebrand factor (vWF) and the stage of cirrhosis. The authors observed significantly higher vWF antigen levels in cirrhotic patients compared to a control group, and also an increase with the increasing stages of cirrhosis according to the Child-Pugh score.…”
mentioning
confidence: 99%
“…These results indicate that vWF is produced as a reliable marker of endothelial dysfunction during hepatocellular failure in cirrhosis. Besides, in light of the results of Yilmaz et al [1] another perspective regarding the low incidence of metastatic malignancy in cirrhotic patients and the potential role of vWF should be pointed out. The blood coagulation protein vWF is mainly secreted by endothelial cells into the subendothelial space and into the plasma, serving as an adhesive link between platelets and the vascular wall.…”
mentioning
confidence: 99%